Mengeksplore aljabar awal di sekolah menengah: kombinasi analisis bibliometric dan meta analisis - Fardian, Dilham; Suryadi, Didi; Prabawanto, Sufyani; Hayuningrat, Silfia (Universitas Hamzanwadi, 2024)
The aims of this study is to analyze publications on early algebra in middle schools to contribute to the development of related literature. A total of 234 articles on early algebra published in various Scopus databases between 2013 and 2024 were retrieved and analyzed through a bibliometric analysis approach and 19 articles through a Comprehensive Meta Analysis (CMA). The results showed fluctuating trends in research related to early algebra in middle schools. The surge in publications using VOSviewer and RStudio from 2013 to 2024 did not align with a corresponding increase in average citations, contributing to a stagnation in the average citation per year. The noticeable upward trend in the volume of publications on early algebra since the beginning of 2013 indicates a dynamic and evolving research landscape in this field. This consistency suggests a widespread and sustained interest in early algebra research beyond the confines of a single country, further emphasizing its global relevance and significance. Integrating multimedia technology into early algebra instruction significantly enhances student learning outcomes. Moreover, access to technology and enhanced learning resources through technology integration can play a more crucial role in improving the effectiveness of early algebra learning in countries with lower income levels.